SnO2 Nanowire Gas Sensor Operating at Room Temperature - Park, Jae-Hwan; Cho, Mun-Seong; Lim, Donggun; Park, Jae-Gwan (AMER SCIENTIFIC PUBLISHERS, 2014)
The NO2 gas sensor based on SnO2 semiconducting nanowires workable at room temperature has been investigated. The network structure of SnO2 nanowires was fabricated on the electrodes by a simple thermal evaporation process from Sn metal powders and oxygen gas. The diameter of the nanowires was 20 similar to 60 nm depending on the processing conditions. When the concentration of NO2 was 10 ppm, the sensitivity of 43, the response time of 38 s, and the recovery time of 25 s were observed at the operating temperature of 200 degrees C. In particular, the operating temperature of the sensor could be decreased down below 50 degrees C by controlling the properties of the nanowires and the structures of the electrodes. The sensitivities were 10 similar to 15 when the NO2 concentrations were 10 similar to 50 ppm at the operating temperature of 50 degrees C.
Keywords: OXIDE; NANOSENSORS